Sea ice study and Arctic polar amplification using BESM model - Fernanda Casagrande (2016)
Important international reports and a significant number of scientific publications have reported on the abrupt decline of the Arctic sea ice, polar amplification and its impact on the Global Climate System. In this thesis, we evaluate the ability of the Brazilian Earth System Model (BESM) to represent the Arctic sea ice and sensitivity to the atmospheric Carbon dioxide (CO$_{2}$) forcing. We used decadal simulations (1980-2012), future scenarios with Representative Concentration Pathway RCP 4.5 and RCP 8.5 (2006-2100) and quadrupling of the atmospheric CO$_{2}$) concentration (2006-2300). We validated our results with satellite observations and compared them to Coupled Model Intercomparison Project, Phase 5 (CMIP5) for the same numerical experiment designs. BESM results for the Arctic sea ice seasonal cycle are consistent with CMIP5 models and observations. However, almost all models tend to overestimate sea ice extent (SIE) in March compared to observations. The correct evaluation of minimum record of sea ice, in terms of time, spatial and area remains a limitation in Coupled Global Climate Models (CGCM). Looking to spatial patterns, we found a systematic model error in September sea ice cover between the Beaufort Sea and East Siberia for most models. Future scenarios show a decrease in SIE as response to an increase in radiative forcing due to the increase of greenhouse gases concentration for all models. From the year 2045 onwards, all models show a dramatic shrinking in sea ice and consequent expansion of ice-free conditions at the end of the melting season. The projected future sea ice loss is explained by the combined effects of both: the amplified warming in northern hemisphere high latitudes and climate feedbacks. The quadrupling of CO$_{2}$) concentration numerical experiment shows the amplified warming at high latitudes as response to CO$_{2}$) forcing with strongest warming in winter (DJF) and Autumn (SON). The Polar warming is linked with changes in SIE and Sea Ice Thickness (SIT). The albedo sea ice feedback reinforces the polar warming with marked contributions from April to August.